Pre- and Post-Conference Practices Amongst Nursing Students During Clinical Practice: A Literature Review - Sudrajat, Diwa Agus; Rizki, Nopia (KnE Life Sciences, 2021)
A conference is a team meeting which is undertaken by nursing staff at every shift change. The conference is conducted before (pre-conference) or after (post-conference) handover. The implementation of this conference has an impact on student skills in reporting plans and results of nursing care during shift changes. This study seeks to acquire an overview of the implementation of pre-conference and post-conference practices by nursing students in clinical practice. This research is a literature review study with five articles. Article ratings are measured using the JBI (The Joanna Briggs Institute Critical Appraisal Tools) format. The literature review was conducted using one database (Google Scholar) for previous studies published in the last 10 years (2010–2020). Of the five articles included in this study, one concluded the discussion pre-conference badly, two concluded the pre-conference was not optimal, and two articles concluded the pre-conference processes were acceptable. For the results obtained in post-conference research, one article did not explain explicitly about the implementation of the post-conference procedures, one concluded that the implementation of the post-conference was not optimal, one concluded that the implementation of the post-conference was quite optimal, and two articles concluded that the post-conference procedures were quite good. It is hoped that the results of this literature review can provide education and information for students, science, educational institutions related to the implementation of the method conference. Nursing students are advised to hold conferences accordingly with standard operating procedures (SOP) for good implementation results Keywords: Nursing Student, conference, clinical practice